Evaluation of the gas porosity and mechanical properties of vacuum assisted pore-free die-cast Al-Si-Cu alloy. (February 2021) - Kang, Ho Jung; Yoon, Pil Hwan; Lee, Gyu Heun; Park, Jin Young; Jung, Byung Jun; Lee, Ji Yong; Lee, Cheol Ung; Kim, Eok Soo; Choi, Yoon Suk
Abstract: High pressure die casting (DC) is an effective manufacturing method suitable for high accuracy, mass production. However, its high injection speeds produce an unstable molten metal flow that induces gas porosity; a critical casting defect that limits the application of heat treatment and welding. In this study, we performed casting using conventional DC(CDC), vacuum assisted DC(VDC), pore-free DC(PFDC), as well as a novel vacuum assisted PFDC(VPFDC). We evaluated the gas porosity of the as-cast and heat-treated specimens using computed tomography, microstructure, and mechanical property analysis. The VDC-, PFDC-, and VPFDC-prepared specimens recorded lower inner gas quantities than that the CDC-prepared specimen; the lowest (4.914 cc/100 g) was recorded for the VPFDC-prepared specimen (product section). X-ray diffraction and optical microscopy analysis showed that the specimens all contained α-Al, eutectic Si, θ-Al2 Cu, and Al2 O3 . However, scanning electron microscopy, transmission electron microscopy, and energy dispersive spectroscopy analysis indicated a higher oxygen content in the PFDC-prepared specimen than the CDC-prepared specimen. Moreover, the tensile properties of the VDC-, PFDC-, and VPFDC-prepared specimens were better than those of the CDC-prepared specimens, and after heat treatment, the tensile properties of the CDC-prepared specimen deteriorated while those of the VDC-, PFDC-, and VPFDC-prepared specimens improved. Highlights: Properties comparison of specimens cast using different casting processes. Vacuum assisted pore-free die casting process minimizes gas porosity of specimens. Pore-free die casting produces specimens with higher oxygen content. Heat treatment improves vacuum-assisted pore-free die cast–parts' tensile strength. Evaluation of a novel vacuum-assisted pore-free die casting process.